Transformation of Penicillium rubens 212 and Expression of GFP and DsRED Coding Genes for Visualization of Plant-Biocontrol Agent Interaction - Villarino, Maria; Espeso, Eduardo A.; Melgarejo, Paloma; Larena, Inmaculada (Frontiers in Microbiology, 2018)
Strain 212 of Penicillium rubens (PO212) is an effective fungal biological control agent against a broad spectrum of diseases of horticultural plants. A pyrimidine auxotrophic isolate of PO212, PO212_18.2, carrying an inactive pyrG gene, has been used as host for transformation by positive selection of vectors containing the gene complementing the pyrG1 mutation. Both integrative and autonomously replicating plasmids transformed PO212_18.2 with high efficiency. Novel PO212-derived strains expressed green (sGFP) and red (Ds-Red Express) fluorescent reporter proteins, driven by the A. nidulans gpdA promoter. Fluorescence microscopy revealed constitutive expression of the sGFP and Ds-Red Express proteins, homogenously distributed across fungal cells. Transformation with either type of plasmid, did not affect the growth and morphological culture characteristics, and the biocontrol efficacy of either transformed strains compared to the wild-type, PO212. Fluorescent transformants pointed the capacity of PO212 to colonize tomato roots without invading plant root tissues. This work demonstrates susceptibility of the biocontrol agent PO212 to be transformed, showing that the use of GFP and DsRed as markers for PO212 is a useful, fast, reliable and effective approach for studying plant–fungus interactions and tomato root colonization.